Synthesis and antimicrobial evaluation of dirithromycin (AS-E 136; LY237216), a new macrolide antibiotic derived from erythromycin. - Counter, F T (1991)
Dirithromycin is a 9-N-11-O-oxazine derivative which is formed by condensation of 9(S)-erythromycylamine with 2-(2-methoxyethoxy)acetaldehyde. Dirithromycin is hydrolyzed, either under acidic conditions or in vivo, to its major active metabolite, 9(S)-erythromycylamine. The antimicrobial spectrum of dirithromycin is similar to that of erythromycin; both antibiotics are active against gram-positive bacteria, Legionella spp., Helicobacter pylori, and Chlamydia trachomatis. Comparable results were obtained for each antibiotic in MIC and MBC determinations and in the potential development of resistance in vitro. The effects of human serum, bacterial growth media, test methodology, and inoculum size on MICs were similar for each antibiotic. In standard mouse protection studies, dirithromycin was more efficacious than erythromycin against experimental infections after subcutaneous administration of antibiotic. These results were consistent with pharmacokinetic studies in rodents, which showed that dirithromycin gave more persistent concentrations of antibiotic in serum and tissues than were achieved with erythromycin. These studies indicate that dirithromycin possesses antimicrobial activity comparable to that of erythromycin in vitro but is more active than erythromycin in vivo, which may be attributable to the persistence of antimicrobial activity in the tissue(s) of the test animals.